2003
DOI: 10.1182/blood-2002-02-0469
|View full text |Cite
|
Sign up to set email alerts
|

In vitro mechanisms of action of rituximab on primary non-Hodgkin lymphomas

Abstract: To assess the sensitivity of primary nonHodgkin lymphoma cells to rituximabmediated cytotoxicity, we compared the potency of several rituximab-mediated killing mechanisms on fresh lymphoma cells. All lymphoma cells tested were equally sensitive to antibody-dependent cell-mediated cytotoxicity (ADCC), antibody-mediated phagocytosis of tumor cells, and rituximab-induced apoptosis. However, they were differentially lysed by complement-dependent cytotoxicity (CDC).We found that taking into account both CD20 and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
243
5
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(263 citation statements)
references
References 32 publications
6
243
5
3
Order By: Relevance
“…Analysis of primary non-Hodgkin's lymphoma cells for their susceptibility to Rituximab-mediated killing showed that Rituximab had a negligible apoptotic effect [15]. Furthermore, the susceptibility of all the cells examined for ADCC did not correlate with the clinical response to the Ab, whereas the in vitro cell-sensitivity to CDC was found to be the best predictor of the in vivo effect of Rituximab [15].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Analysis of primary non-Hodgkin's lymphoma cells for their susceptibility to Rituximab-mediated killing showed that Rituximab had a negligible apoptotic effect [15]. Furthermore, the susceptibility of all the cells examined for ADCC did not correlate with the clinical response to the Ab, whereas the in vitro cell-sensitivity to CDC was found to be the best predictor of the in vivo effect of Rituximab [15].…”
Section: Introductionmentioning
confidence: 97%
“…Analysis of primary non-Hodgkin's lymphoma cells for their susceptibility to Rituximab-mediated killing showed that Rituximab had a negligible apoptotic effect [15]. Furthermore, the susceptibility of all the cells examined for ADCC did not correlate with the clinical response to the Ab, whereas the in vitro cell-sensitivity to CDC was found to be the best predictor of the in vivo effect of Rituximab [15]. The important role of CDC in mediating the therapeutic effect of Rituximab was supported by the finding that the growth of a murine lymphoma transfected with CD20 was inhibited by Rituximab in complement-sufficient but not in C1q-deficient mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various in vitro and in vivo experiments have shown that elimination of CD20þ lymphoma cells by rituximab involves complement-dependent cytotoxicity (CDC; refs [16][17][18][19][20][21][22][23], direct induction of apoptotic signalling (24)(25)(26), as well as the recruitment of effector cells leading to antibody-dependent cell-mediated cytotoxicity (27). Nevertheless, the in vivo mechanism of action of and resistance to rituximab are not fully understood (28).…”
Section: Introductionmentioning
confidence: 99%
“…Different factors may contribute to this therapeutic failure of CD20-targeted therapies, including CD20 downregulation (Foran et al, 2001), altered signal transduction pathways (Pommier et al, 2004), circulating CD20 protein (Manshouri et al, 2003), polymorphisms in the FcgRIII receptor (Cartron et al, 2002) and an increase in complement-resistant proteins like CD55 or CD59 (Treon et al, 2001;Manches et al, 2003). The immunohistochemical analysis of the presented case series of relapsing CBCL lesions revealed an unchanged CD20 expression.…”
Section: Discussionmentioning
confidence: 73%